Perancangan Tas Multiguna Menggunakan Studi Gerak dan Waktu - Khodijah, Tiara; Farras Chanira, Siti; Jihan Asy’ari, Muhammad; Rizky Pramono, Aqilla; Belasunda, Riksa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Adapting to a new lifestyle due to new normal conditions requires the implementation of health protocols by each individual to prevent the spread of the Covid-19 virus. One of the steps that can be taken to avoid transmission is to bring your own personal equipment, considering that some public places have implemented health protocols and do not provide personal items in general. In this context, a bag that can efficiently accommodate luggage is needed. From these observations, it appears that multifunctional bag design is very important during this pandemic. This research uses a comparative study method of several existing products by applying the time and motion study method. The results showed that common problems involved overloading, which can damage the bag and cause shoulder discomfort, and lack of adequate compartments. These findings were used as a basis to develop a multifunctional bag with an emphasis on comfort and the addition of adequate compartments to support productive activities both inside and outside the home.